Effect of Erythritol on Glucosyl Transferase and Fructosyl Transferase Gene Expression in Streptococcus mutans - Young-Nam PARK; Jae-Ki RYU (Korean Journal of Clinical Laboratory Science, 2023)
Erythritol is a sweetener produced by yeast from glucose and a natural sugar found in fermented foods such as mushrooms, wine, fruits, rice wine, and soy sauce. Correct information and basic data when producing or using products for preventing dental caries by checking the gene expression patterns of glucosyl transferase (GTF) and fructosyl transferase (FTF) of Streptococcus mutans in erythritol and other sweeteners it was implemented to provide. Erythritol inhibited the growth of Streptococcus mutans, which is involved in dental caries. When used as a sweetener to replace sucrose, erythritol had an excellent caries-preventative effect. In particular, erythritol reduced the expressions of gtfB, gtfC, gtfD, and FTF, which are related to the synthesis of extracellular polysaccharides, and thereby reduced the formation of dental plaque and the attachment rate of bacteria to tooth surfaces. The study shows erythritol has potential use as an anticariogenic sweetener that inhibits the mechanism underlying caries caused by Streptococci.